Numerical Impact Assessment Based on Experiments for Steel Stiffened Panels with and Without Prior Dent - Sara A. Eltawosy; Heba S. El-Kilani; Elsayed Fathallah; S. Saad-Eldeen (Journal of Marine Science and Engineering)
Many ship panels may be subjected to operational or accidental impact loads, and increased crashworthiness is a desirable design feature. A designer may reach this goal using different structural configurations that are available nowadays. However, the selection of the appropriate design parameters is not simple, due to the complexity of predicting impact response. This research is based on published experimental crashworthiness results of a steel stiffened panel tested under low-velocity impact loading. A series of finite element analyses is performed to develop a master model that can be applied to different parameters. The results showed good agreement between the developed finite element model and the experimental results, which confirms the accuracy and reliability of the numerical model. A parametric study is carried out to investigate the effect of design parameters such as plating thickness, stiffener section modulus, stiffener spacing, and stiffener profiles on the crashworthiness characteristics of the calibrated model, and the geometrical configurations that offer the best crashworthiness without considerable increased weight may be then determined based on a proposed criterion. To cover complex realistic scenarios during operation, pre-existing mechanical damage consisting of a specified dent is applied to the intact panel, to check the survivability of the proposed model with respect to the intact one. Finally, simplified design guidelines are proposed to improve both the safety and structural integrity characteristics of the structural configurations considered.